Influenza vaccination and prevention of antimicrobial resistance - Susanna Esposito; Nicola Principi (Taylor & Francis Group, 2018)
Introduction: Abuse and misuse of available antimicrobial drugs have increased antimicrobial resistance (AMR), with relevant adverse health and economic impacts. Several factors suggest that the influenza vaccine is a possible effective measure to control AMR through a significant reduction in antibiotic consumption. In this paper, aspects related will be discussed. Areas covered: Although the effectiveness of influenza immunization can significantly vary according to the study design, the circulating influenza viruses, the type of vaccine, the age of the enrolled subjects, the outcome measured and the season of the study, all experts agree that the influenza vaccine can significantly reduce the risk of contracting influenza in subjects of any age. Consequently, influenza vaccination may reduce the number of bacterial superimposed infections that can complicate influenza and require antibiotic prescriptions. Expert commentary: Several indirect and direct observations seem to indicate that influenza vaccines can play an important role in reducing influenza-related antibiotic prescriptions. This finding can lead to at least two undeniable advantages, reductions in drug expenditure and limitations of the risk of favoring AMR development. However, only when universal vaccination is accepted and implemented will the true advantages of the influenza vaccine in reducing AMR development be completely known and exploited.